2021
DOI: 10.1002/anie.202111181
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Low Driving Force in Forming Depolymerizable Polymers through Monomer Isomerization

Abstract: While depolymerizable polymers have been intensely pursued as ap otential solution to address the challenges in polymer sustainability,m ost depolymerization systems are characterized by alow driving force in polymerization, which poses difficulties for accessing diverse functionalities and architectures of polymers.H ere,w ea ddress this challenge by using ac yclooctene-based depolymerization system, in which the cis-to-trans alkene isomerization significantly increases the ring strain energy to enable living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
1
48
0
1
Order By: Relevance
“…Sequentially, Wang also found that the cis-to-trans alkene isomerization of these monomers significantly increased the ring strain energy, enabling ring-opening metathesis polymerization to occur at a relatively low monomer concentration. 221 More recently, Wang has also discussed the structure-polymerization thermodynamics relationship of fused-ring cyclooctenes and extended the polymerizationdepolymerization cycle to a series of new monomers, such as M6 and M7. 222…”
Section: Chemically Recyclable Polymer Derived From Eight-membered Ri...mentioning
confidence: 99%
“…Sequentially, Wang also found that the cis-to-trans alkene isomerization of these monomers significantly increased the ring strain energy, enabling ring-opening metathesis polymerization to occur at a relatively low monomer concentration. 221 More recently, Wang has also discussed the structure-polymerization thermodynamics relationship of fused-ring cyclooctenes and extended the polymerizationdepolymerization cycle to a series of new monomers, such as M6 and M7. 222…”
Section: Chemically Recyclable Polymer Derived From Eight-membered Ri...mentioning
confidence: 99%
“…通过环辛二烯与马来酸酐发生 2+2 环加成反 应构建反式环辛烯并四元环结构, 然后发生转化得到不 同功能单体, 其可以在 G2 的催化下顺利发生聚合反应 得到 M n >100 kg/mol 的聚合物, 但是分子量分布很宽 (Ɖ>1.5). 随后研究发现, 通过光照使顺式烯烃异构化 为反式烯烃(图 23), 而反式烯烃环张力增加可以在该聚 合条件下实现活性聚合 [177] . 机械性能测试表明, 改变 四元环上取代基的结构, 聚合物为弹性体或者聚苯乙烯 类似机械性能.…”
Section: 闭环回收的含硫高分子unclassified
“…Another unique feature of this system is that the driving force for polymerization can be elevated by isomerizing the cis -cyclooctene to its trans form, allowing the polymerization to be conducted in dilute monomer concentrations (≥25 mM). 32 Herein, we leverage the versatility of the t CBCO system and report chemically recyclable semi-fluorinated polymers (Fig. 1b, P1–P3 ).…”
Section: Introductionmentioning
confidence: 99%